ARTIFICIAL INTELLIGENCE IN DISTRIBUTED TEAMS: ENHANCING COMMUNICATION AND COORDINATION IN GLOBAL PROJECT ENVIRONMENTS (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article reviews current research on human -AI teaming, AI- mediated communication, and the use of chatbots to support distributed teams. Key mechanisms for improving team efficiency are identified, as well as risks associated with privacy, trust, and responsibility allocation. Practical recommendations for implementing AI in project management in global organizational environments are formulated.